Wanted: Scientists with human touch - Abd Razak, Dzulkifli (2008)
OVER the last few weeks, the subject of science and innovation has been the theme of a number of conferences and seminars. Under the initiative taken by the Science, Technology and Innovation Ministry, a case has been made for an innovationdriven economy which will hopefully take Malaysia to greater heights. This has been the case of many developed economies where science and technology act as the driving force. As a nation progresses, it is inevitable that they will transit from a resourcebased economy to one that is innovationbased. The former is more dependent on tangibles like labour, land, resources and machines. The latter depends on intangibles such as talent, ideas and knowledge.